19. QUALITY OF LIFE OF THE OLDER PEOPLE WITH CARDIOVASCULAR DISEASES IN THAI BINH (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the quality of life of older people with cardiovascular diseases in Thai Binh province in 2024.Subjects and research methods: A cross-sectional study in the community. The research subjects were 264 older people (≥ 60 years old) with cardiovascular diseases living in 5 communes in Dong Hung district, Thai Binh, from April 2024 to June 2024.Results: The average score of the quality of life of the older people with cardiovascular diseases in general (0.5431) was significantly lower than the quality of life of the older people aged 65 years and older in the general population (0.89), as well as significantly lower than the quality of life of the older people with cardiovascular diseases in Hanoi (0.7176). Only people with rheumatic heart disease had a better quality of life (0.8351). The diseases that have the most significant impact on the lives and activities of patients are cerebrovascular disease (0.2325), pulmonary heart disease, and pulmonary circulation (0.2308). Anxiety, sadness, pain, and/or discomfort are the factors that most affect the quality of life.Conclusion: Health education and propaganda efforts are necessary to help older people comprehend the illness and feel comfortable receiving treatment, in order to improve their quality of life.
Keywords: Quality of life; older people; cardiovascular diseases; EQ-5D-5L.